(untitled) - Welch, Patrick J. (Orlando, Florida, 1998)
Newly updated, the Seventh Edition of Economics: Theory and Practice introduces students to basic economic concepts, institutions, relationships, and terminology. Covering a range of timely subjects and featuring engaging pedagogical tools, this book prepares students to use economic thinking in their classes, careers, and everyday lives. Through six editions, students have cited the text as exceptionally user-friendly and readable.
Keywords: Economics